Measuring economic uncertainty for Poland - Stanis±aw Bartha; Maria Elena Bontempi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
Measuring economic uncertainty is challenging, but it is important for policymakers to address it, especially in countries for which there are virtually no uncertainty indices. This article proposes an index of economic uncertainty for Poland, EURQPL, based on Internet searches for specific terms to capture the level of uncertainty perceived by Internet-using economic agents. Compared to Bontempi et al. (2021) who analysed the US and Italy, the change of country, the use of either Polish or English in the definition of queries and the creation of regional indices offer interesting insights. The national index peaks at times commonly considered uncertain, such as the financial crisis and the coronavirus pandemic. Compared to the EURQ for the US and Italy, our index has a significant peak due to the teachers' strike, a shock not reported in the literature. Particularly relevant are the terms related to social security and fiscal policy; uncertainty shocks have persistent effects on unemployment. Besides confirming how successfully Internet searches can be exploited in economic research, we highlight how regional indices can be used to study the impact of uncertainty on local economies.
Keywords: C23; C41; D22; G32; L10; O30; 330; Economic Uncertainty; Uncertainty in Poland; Regional Uncertainty; Native Language and English; Internet Searches; Google Trends